First results of the signal processing of INDERA - Sediono, Wahju; Lestari, Andrian Andaya (2009)
INDERA is the first Indonesia's maritime radar designed to be installed and operated on a ship. This radar is based on the FMCW principle for which a reliable method for processing the radar signal plays an important role. In this paper the method used for processing radar signals received by the Rx-antenna is discussed. Thereafter first results from the field test of INDERA will be presented at the end of the method description.